Lupus Flare: An Uncommon Presentation of Disseminated Gonorrhea - Uyen To; Joyce Kim; David Chia (Case Reports in Medicine)
Gonorrhea is one of the most common sexually transmitted diseases in the US with 700,000 annual cases. Although most cases of gonorrhea are localized, approximately 0.5–3% become disseminated. Here we discuss a rare case of a patient with systemic lupus erythematosus (SLE) who developed septic shock from disseminated gonorrhea infection (DGI). Our patient is a 24-year-old woman with SLE, mixed connective tissue disease with cutaneous vasculitis, and lupus nephritis who presented with several weeks of malaise and generalized body aches associated with a diffuse rash along her fingers, palms, and trunk. Infectious workup was unrevealing with the exception of a positive gonorrhea test obtained from a cervical swab. Given her symptoms of tenosynovitis, the appearance of her skin lesions, and her positive gonorrhea test, she was diagnosed with septic shock secondary to DGI. With antibiotic treatment, the patient reported a dramatic improvement of the pain in her swollen joints and her rash receded. Patients diagnosed with SLE carry an increased risk of gonorrhea regardless of whether or not they are being treated for their SLE. Although it is well-documented that SLE is associated with severe DGI, few describe it resulting in overt septic shock.